Gradient ordered membrane electrode construction and integration method for PEM electrolyzed water
Through the gradient ordered film electrode construction and integration method, the problems of high cost of precious metals and uneven current density in PEM electrolytic technology are solved, and low-cost, high-efficiency and long-life membrane electrodes are realized.
Patent Information
- Application Number
- CN202311393689.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-25
AI Technical Summary
In the existing PEM electrolytic technology, the anode material uses expensive precious metals, which leads to high costs, and the contact between the catalytic layer and water/gas in large-sized film electrodes is uneven, resulting in uneven current density and reduced stability.
The gradient ordered film electrode construction and integration method is adopted to tune the local thickness and water/gas ratio of the catalytic layer through the gradient template method to achieve efficient utilization of the catalyst and uniformity of current density.
The efficiency of the catalyst utilization is improved, a highly uniform current density is achieved, cost is reduced, and the stability of the membrane electrode is enhanced.
Smart Images

Figure CN119876990A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of membrane electrodes, and in particular to a method for constructing and integrating a gradient ordered membrane electrode for PEM water electrolysis. Background Art
[0002] Hydrogen energy is an important component of my country's future energy composition. How to achieve efficient hydrogen energy production is crucial to achieving the "dual carbon" goal. PEM water electrolysis has become a very promising hydrogen energy generation device with its high current density and high coupling potential with renewable energy (intermittent energy such as solar energy, wind energy, and tidal energy) (Science 2016(353),1011-1014). However, the anode materials in PEM water electrolysis technology often use expensive iridium and ruthenium precious metals, resulting in high costs. Especially in high-power electrolysis stack applications, due to the significant increase in the area of a single cell, mass transfer is limited. This problem becomes more and more significant as the total current increases. A higher total current not only means faster water decomposition, but also means more gas accumulation in the flow channel, and the catalyst layer at the far end of the water inlet is difficult to fully contact with water. This problem not only leads to a decrease in catalyst utilization and an increase in cost, but also leads to uneven current density distribution. Current compensation at the water inlet causes a sudden increase in local current density and temperature, and a decrease in stability.
[0003] How to combine the operating conditions of large-scale membrane electrode and fuel cell stack, design a membrane electrode structure that meets application requirements, reasonably tune the relationship between the thickness of the catalyst layer and the distribution of the water / gas ratio on the interface, and achieve cost savings and efficiency improvement in PEM water electrolysis devices is the key to promoting the application of PEM water electrolysis devices.
[0004] Compared with small-sized membrane electrodes, the core problem faced by large-sized membrane electrodes and fuel cells is that the water-gas ratio of the catalyst layer to the reactants decreases as the time it stays inside the membrane electrode increases. The uneven current density caused by this seriously limits the integration of high-performance devices. The disordered arrangement of catalysts in the catalyst layer not only limits the diffusion and release of water / gas molecules in it, but also reduces the transmission efficiency of electrons / protons, resulting in increased internal resistance of the electrolytic cell and decreased performance. Therefore, it is necessary to construct a gradient-ordered catalyst layer to ensure that while maintaining high charge-mass transfer performance, the number of catalytic sites in different areas of the catalytic interface is tuned to match the gradually decaying concentration of water molecules, so as to fully utilize the active sites and improve the uniformity of the current density, ensuring that the activity of the membrane electrode can be efficiently expressed in the fuel cell.
[0005] At present, the technical research and development is mainly focused on the construction of ordered membrane electrodes. The ordering method that is closer to this patent is the template method. Patent CN115125549A constructs a one-dimensional ordered template by etching a titanium plate and loads the catalyst on it. By transferring the catalyst array to the proton exchange membrane, the loading of a one-dimensional low-iridium ordered nanoarray on the membrane electrode is achieved, 1A / cm 2 The performance is improved by 60mV (1.933V to 1.872V). Patent CN112981449A achieves 1A / cm by electrodepositing catalyst on the surface of ordered transition metal oxides. 2 The overpotential is less than 1.8 V. However, these methods do not consider the impact of the internal gradient decrease of the large-sized membrane electrode flow channel.
[0006] PEM water electrolysis devices need to maintain high current density, low energy consumption, low cost and high stability when facing applications. However, as the current density increases, the water / gas ratio near the water outlet inside the PEM water electrolysis device will be significantly lower than the water inlet. The catalyst layer area in contact with the reactants with a lower water / gas ratio is difficult to fully express its own performance, resulting in reduced catalyst utilization and limited device performance. This situation will also be aggravated as the size of the membrane electrode increases, and may even cause the catalyst layer near the water outlet to be completely unable to contact water, which not only increases the energy consumption and cost of the device, but also reduces the upper limit of the device. In addition, the decreased water / gas ratio will also lead to a decrease in current density. When the device produces hydrogen at high power, due to the low water / gas ratio near the water outlet, the local current density is small, and compensation is required near the water inlet, resulting in excessively high local current density and reduced device stability.
[0007] Based on this, the present invention has created an ordered gradient membrane electrode construction and integration process, which uses the gradient template method to multi-dimensionally tune the relationship between the local thickness of the catalytic layer and the water / gas ratio, improves the catalyst utilization efficiency and achieves highly uniform current density. Combined with the matching optimized flow field structure, it improves the performance expression of large-size membrane electrodes under working conditions, and realizes the construction of low-cost, high-efficiency, and long-life PEM water electrolysis membrane electrodes. Summary of the invention
[0008] The present invention is to overcome the defects in the prior art and provide a method for constructing and integrating a gradient ordered membrane electrode for PEM water electrolysis. The present invention is achieved through the following technical solutions:
[0009] In the first aspect, the present invention provides a gradient ordered membrane electrode for PEM water electrolysis, comprising a gradient ordered anode catalyst layer, wherein the anode catalyst layer is composed of a plurality of ordered regions, the catalyst layer of each ordered region is composed of a uniformly distributed nanoarray, the height of the nanoarray in each ordered region is the same, and the thickness gradient of the catalyst layer in the ordered region increases from the liquid inlet to the liquid outlet.
[0010] Preferably, the gradient ordered membrane electrode for PEM water electrolysis also includes an ordered cathode catalyst layer, the cathode catalyst layer is ordered as a whole, the cathode catalyst layer is composed of uniformly distributed nanoarrays, and the height of the nanoarrays in the entire cathode catalyst layer is the same.
[0011] Preferably, the density of the nanoarray in the anode catalyst layer is 10,000 nanoarrays / cm 2 ~10 12 Root / cm 2 The diameter of the nanocolumns constituting the nanoarray is 3nm~100μm, the gap between the nanoarray is 1nm~100μm, and the density of the nanoarray in the cathode catalyst layer is consistent with that in the anode catalyst layer.
[0012] Preferably, the thickness of the anode catalyst layer increases gradually, with the increasing direction being perpendicular to the flow field direction. The thickness is controlled by the height of the nanoarray in each ordered region. The thickness of the initial catalyst layer is 0.001 mm to 0.2 mm, and the thickness of the terminal catalyst layer is 0.2 mm to 1.0 mm.
[0013] In a second aspect, the present invention provides a method for constructing and integrating a gradient ordered membrane electrode for PEM water electrolysis, the steps of which are as follows:
[0014] Step S1, preparing anode template
[0015] S1.1 According to the actual load size D×L, select N suitable substrates, each of which has a width of D / N and a length of L; where D is the width of the electrode, L is the length of the electrode, and N is a positive integer greater than 2;
[0016] S1.2 Prepare an ordered nanoarray growth solution or a substrate ordered etching solution, construct array channels by hydrothermal method or ordered etching method, and adjust the size of the nanoarray by controlling the processing time to obtain an ordered template sequence; the processing time is the hydrothermal processing time or the etching processing time, and the processing time of the nth substrate is Wherein, n is any positive integer from 1 to N, t is the processing time of the first substrate, and T is the processing time of the Nth substrate;
[0017] S1.3 The anode slurry is impregnated or sprayed on the template, and the anode catalyst is loaded on N ordered template sequences, and the loading amount increases with the extension of the template treatment time. The ordered template sequences are arranged in the order of treatment time to assemble into an anode template with an actual loading size of D×L;
[0018] Step S2, preparing cathode template
[0019] Step S3, preparing membrane electrode
[0020] Step S4, integration
[0021] S4.1 Calibrate the membrane electrode thickness in each gradient range by using a spiral micrometer, and customize the corresponding flow field after clarifying the thickness gradient, so that the sum of the flow field thickness at both poles and the membrane electrode thickness is the same in each area;
[0022] S4.2 Place and assemble the membrane electrode / stack in the order of increasing anode loading from the water inlet to the water outlet.
[0023] Preferably, the substrate in step S1 and / or step S2 is selected from niobium plate, aluminum plate, tungsten plate, titanium plate, tantalum plate, platinum plate, and iridium plate.
[0024] Preferably, in step S1 and step S2, the substrate is cleaned and activated. More preferably, the cleaning and activation method is to first polish to a mirror surface and then treat with hydrogen peroxide. More preferably, the concentration of hydrogen peroxide is 0.5% to 20%.
[0025] Preferably, in step S1.2, the ordered nanoarray growth solution is chloride, sulfate, phosphate, acetate and corresponding salts of niobium, tungsten, titanium, tantalum, platinum, zirconium, chromium and manganese.
[0026] Preferably, the corresponding salt is tungstate, fluorotantalate, or chloroplatinate.
[0027] Preferably, the concentration of the ordered nanoarray growth solution is 0.1M-3M.
[0028] Preferably, in step S1.2, the hydrothermal treatment method is to place the substrate and urea, oxalic acid or oxalate in the ordered nanoarray growth solution, the molar ratio of urea, oxalic acid or oxalate to the metal salt is 1:1 to 10:1, the hydrothermal temperature is 80 to 200°C, the hydrothermal treatment time t of the first substrate is 1-8h, and the hydrothermal treatment time T of the Nth substrate is 12-36h.
[0029] Preferably, in step S1.3, the anode slurry includes a catalyst or a catalyst precursor, specifically, a composite oxide, alloy, chloride, acetylacetonate, nitrate, acetate, or sulfate of iridium or ruthenium.
[0030] Preferably, step S2 comprises the following steps:
[0031] S2.1 uses a base plate with actual load size D×L,
[0032] S2.2 preparing an ordered nanoarray growth solution or a substrate ordered etching solution, constructing array channels by a hydrothermal method or an ordered etching method, and obtaining a template;
[0033] S2.3 The catalyst and ionomer are grown and loaded on the template using an immersion method or a spraying method. The cathode catalyst is loaded on the surface of the template, and the loading amount does not vary with the region.
[0034] Preferably, in step S2.3, the cathode slurry includes a catalyst or a catalyst precursor, specifically a composite oxide, alloy, chloride, acetylacetonate, nitrate, acetate, or sulfate of platinum.
[0035] Preferably, the average mass ratio of the precious metal loading in the cathode template to that in the anode template is between 1:4 and 1:1.
[0036] Preferably, step S2 comprises the following steps:
[0037] S3.1 The cathodic catalyst and the anodic catalyst are transferred to the surface of the proton exchange membrane by a transfer method to obtain a membrane electrode;
[0038] S3.2 Soak the membrane electrode in dilute acid to remove unstable impurities, and then soak it in deionized water to swell for later use.
[0039] Preferably, the concentration of the dilute acid is 0.5M.
[0040] As a preference, the noble metal loading in the nth ordered template sequence is mST n / ΣT n , m is the average load per unit area, which is set according to the actual situation, S is the actual load area D×L, T n is the hydrothermal treatment time of the nth substrate, m is 0.1 mg / cm 2 ~4mg / cm 2
[0041] Preferably, the anode slurry and the cathode slurry further include ionomer, and the mass of the ionomer accounts for 5% to 30% of the total mass of the catalyst and the ionomer.
[0042] Preferably, the step of impregnating and spraying the anode slurry on the template in S1.3 also includes a step of sintering in a muffle furnace, the sintering temperature is 300-800° C., and the sintering time is 1-6 hours.
[0043] Preferably, in step S3.1, the transfer pressure is 0.1 to 3 t / cm 2, the transfer temperature is 120-135°C, and the transfer time is 1-10 minutes.
[0044] Preferably, in step S3.2, the soaking time is 2 to 24 hours.
[0045] Preferably, in step S4.1, the sum of the thickness of the flow channel and the thickness of one side of the membrane electrode is 0.1 mm to 5 mm.
[0046] Preferably, a serpentine flow field is used, and the width of the serpentine flow field is D / (N×X), where X is the number of times the flow field on the surface of each gradient catalyst passes through.
[0047] Preferably, X is an integer of 2-10.
[0048] Preferably, the straight flow channel portion of the serpentine flow field is perpendicular to the water inlet and outlet directions.
[0049] Therefore, the present invention has the following beneficial effects:
[0050] (1) In the present invention, a gradient is set in the ordered membrane electrode, and the relationship between the local thickness of the catalyst layer and the water / gas ratio is tuned in multiple dimensions based on the gradient template method, thereby improving the catalyst utilization efficiency and achieving a highly uniform current density; the thickness of the catalyst layer increases with the flow channel gradient, the site utilization rate increases, the cost is reduced, and the current density in each area of the catalyst layer is uniform, thereby enhancing the stability of the membrane electrode.
[0051] (2) The present invention adopts a serpentine flow field, and the sum of the flow channel of the flow field and the thickness of the membrane electrode does not change, which improves the performance of large-size membrane electrodes under working conditions and realizes the construction of low-cost, high-efficiency, and long-life PEM water electrolysis membrane electrodes.
[0052] (3) The flow field design principle matches the catalyst layer. The flow field thickness becomes thinner as the catalyst layer thickens and the water molecule concentration decreases. While ensuring the consistency of the local thickness of the electrolytic cell, the pressure is appropriately increased in the low water / gas ratio area to increase the water molecule concentration and improve performance.
[0053] (4) The graded template method is used to construct a size-controllable nanoarray. This synthesis method is easy to scale up for mass production and has high commercial value. Since each section of the gradient template sequence is prepared and tailored individually, it is highly controllable and easy to scale up for production. It can be precisely optimized and regulated according to usage requirements.
[0054] (5) Strong universality. This synthesis strategy can adjust the substrate size and material according to actual usage requirements, and adjust the thickness according to the current density requirements of different working conditions. The substrate can also be cut after batch processing to facilitate mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 It is a schematic diagram of the side view structure of the gradient ordered membrane electrode in the present invention;
[0056] Figure 2 This is a schematic diagram of the top view of the OER side of the gradient ordered membrane electrode in the present invention;
[0057] Figure 3 Comparison of the polarization performance of the gradient ordered membrane electrode prepared in Example 1 of the present invention with that of the conventional uniform coating method;
[0058] Figure 4 It is a schematic diagram of the gradient electrode and the flow direction of the liquid in the flow field in the present invention;
[0059] Figure 5 It is a schematic side view of the gradient membrane electrode and flow field composite structure in the present invention. DETAILED DESCRIPTION
[0060] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments of the specification. Those of ordinary skill in the art will be able to implement the present invention based on these descriptions. In addition, the embodiments of the present invention involved in the following description are generally only embodiments of a part of the present invention, rather than all embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work should fall within the scope of protection of the present invention.
[0061] Embodiment 1:
[0062] Cut 10 10cm*1cm niobium plates with a thickness of 0.5cm, polish them and soak them in 10% hydrogen peroxide solution for cleaning, then prepare 30mL 1M potassium fluorotantalate, add equimolar urea to it, and hydrothermally react the ten niobium plates in it, the hydrothermal treatment temperature is 160℃, the hydrothermal treatment time is (10n+8) / 9 (n=1~10, t=2, T=12), specifically 2h, 28 / 9h, 38 / 9h, 16 / 3h, 58 / 9h, 68 / 9h, 26 / 3h, 88 / 9h, 98 / 9h and 12h respectively. After rinsing and drying with ultrapure water, each template is equally impregnated with adsorbed anode slurry. The anode slurry includes ink, catalyst and Nafion ionomer. The catalyst is iridium oxide. The ink consists of isopropanol and water in a volume ratio of 3:1. The ink is liquid, the catalyst and Nafion ionomer are solid, and the ratio of solid to liquid is 10 mg / mL. The mass of Nafion ionomer accounts for 15% of the total solid mass. The mass of each template adsorbed catalyst is (55*(5n+4) / Σ(5n+4)) mg (n=1-10), specifically 11 / 7 mg, 154 / 63 mg, 209 / 63 mg, 88 / 21 mg, 319 / 63 mg, 374 / 63 mg, 143 / 21 mg, 484 / 63 mg, 539 / 63 mg, 66 / 7 mg. Dry and set aside.
[0063] Cut another 10cm*10cm niobium plate with a thickness of 0.5cm, polish it and soak it in a 10% hydrogen peroxide solution for cleaning, then prepare 30mL1M potassium fluorotantalate, add an equal number of moles of urea to it, and hydrothermally react the niobium plates in it, the hydrothermal treatment temperature is 160℃, and the hydrothermal treatment time is 10 hours. After rinsing and drying with ultrapure water, the template is equally impregnated with adsorbed cathode slurry. The cathode slurry includes ink, catalyst and Nafion ionomer. The catalyst is a 40% platinum carbon catalyst (40% is the mass ratio of heavy metal platinum to platinum carbon catalyst). The ink is liquid, the catalyst and Nafion ionomer are solid, and the ratio of solid to liquid is 10mg / ml. The ink is composed of isopropanol and water in a volume ratio of 3:1. The mass of Nafion ionomer accounts for 15% of the total solid mass. The adsorption amount of catalyst on the template is 1mg / cm 2 , dry and set aside.
[0064] The catalytic layer was transferred to the Nafion membrane by transfer method, with transfer pressure of 10t, transfer temperature of 135℃ and time of 3min. Then the membrane was soaked in 0.5M sulfuric acid for 10h and soaked in clean water for standby use. The sum of the channel thickness and the membrane electrode thickness was controlled to be 1mm. The straight channel part of the serpentine channel was controlled to be perpendicular to the water inlet and outlet directions, and the membrane electrode was assembled and tested.
[0065] The performance of the membrane electrode prepared in Example 1 was tested and compared with that of the membrane electrode prepared by the conventional method. Figure 3 As shown, the performance of the gradient ordered membrane electrode is significantly improved, and the degree of improvement further increases with the increase of current density.
[0066] Embodiment 2:
[0067] Cut 10 10cm*1cm tungsten plates with a thickness of 0.5cm, polish and soak them in 10% hydrogen peroxide solution for cleaning, then prepare 30mL 1M sodium tungstate, add 2 times the mole of urea, and hydrothermally react the ten niobium plates in it, the hydrothermal treatment temperature is 180℃, the hydrothermal treatment time is (10n+8) / 9 (n=1~10, t=2, T=12), specifically 2h, 28 / 9h, 38 / 9h, 16 / 3h, 58 / 9h, 68 / 9h, 26 / 3h, 88 / 9h, 98 / 9h and 12h. After rinsing and drying with ultrapure water, each template is equally impregnated with adsorbed anode slurry. The anode slurry includes ink, catalyst and Nafion ionomer. The catalyst is iridium oxide. The ink is liquid, the catalyst and Nafion ionomer are solid, and the ratio of solid to liquid is 10mg / ml. The ink is composed of isopropanol and water in a volume ratio of 3:1. The mass of Nafion ionomer accounts for 20% of the total solid mass. The mass of each template adsorption catalyst is (110*(5n+4) / Σ(5n+4))mg (n=1-10), specifically 22 / 7mg, 308 / 63mg, 418 / 63mg, 176 / 21mg, 638 / 63mg, 748 / 63mg, 286 / 21mg, 968 / 63mg, 1078 / 63mg, 132 / 7mg. Dry and set aside.
[0068] Cut another 10cm*10cm tungsten plate with a thickness of 0.5cm. After polishing, soak it in a 10% hydrogen peroxide solution for cleaning. Then prepare 30mL of 1M sodium tungstate, add 2 times the molar number of urea to it, and hydrothermally react the niobium plate in it. The hydrothermal treatment temperature is 180℃ and the hydrothermal treatment time is 8 hours. After rinsing and drying with ultrapure water, the template is equally impregnated with adsorbed cathode slurry. The cathode slurry includes ink, catalyst and Nafion ionomer. The catalyst is a 40% platinum carbon catalyst (40% is the mass ratio of heavy metal platinum to platinum carbon catalyst). The ink is liquid, the catalyst and Nafion ionomer are solid, and the ratio of solid to liquid is 10mg / ml. The ink is composed of isopropanol and water in a volume ratio of 3:1. The mass of Nafion ionomer accounts for 20% of the total solid mass. The adsorption amount of catalyst on the template is 1mg / cm 2 , dry and set aside.
[0069] The catalytic layer was transferred to the Nafion membrane by transfer method with transfer pressure of 15t, transfer temperature of 135℃ and time of 2min. The membrane was then soaked in 0.5M sulfuric acid for 10h and soaked in clean water for standby use. The sum of the channel thickness and membrane electrode thickness was controlled to be 1mm. The straight channel part of the serpentine channel was controlled to be perpendicular to the water inlet and outlet directions for membrane electrode assembly and testing.
[0070] The performance of the membrane electrode prepared in Example 2 was tested, and the results were similar to those in Example 1.
[0071] Embodiment 3:
[0072] Cut 20 10cm*0.5cm niobium plates with a thickness of 1cm, polish them, soak them in 5% hydrogen peroxide solution for cleaning, and then prepare 30mL 1M aluminum sulfate, add oxalic acid in equal moles, and hydrothermally react twenty niobium plates therein, the hydrothermal treatment temperature is 120°C, the hydrothermal treatment time is (10n+104) / 19 (n=1-20, t=6, T=16), specifically 6h, 124 / 19h, 134 / 19h, 144 / 19h, 154 / 19h, 164 / 19h, 174 / 19h, 184 / 19h, 194 / 19h, 204 / 19h, 214 / 19h, 224 / 19h, 234 / 19h, 244 / 19h, 254 / 19h, 264 / 19h, 274 / 19h, 284 / 19h, 294 / 19h, 16h. After rinsing and drying with ultrapure water, each template is equally impregnated with adsorption anode slurry. The anode slurry includes ink, catalyst and Nafion ionomer. The catalyst is iridium oxide. The ink is liquid, the catalyst and Nafion ionomer are solid, and the ratio of solid to liquid is 10 mg / ml. The ink is composed of isopropanol and water in a volume ratio of 3:1. The mass of Nafion ionomer accounts for 15% of the total solid mass. The mass of catalyst adsorbed on each template is (10(10n+104) / 209) mg (n=1-20). Dry and set aside.
[0073] Cut another 10cm*10cm niobium plate with a thickness of 1cm, polish it and soak it in a 10% hydrogen peroxide solution for cleaning, then prepare 30mL of 1M aluminum sulfate, add an equal number of moles of oxalic acid to it, and hydrothermally react the niobium plates in it, the hydrothermal treatment temperature is 120℃, and the hydrothermal treatment time is 8 hours. After rinsing and drying with ultrapure water, the template is equally impregnated with adsorbed cathode slurry. The cathode slurry includes ink, catalyst and Nafion ionomer. The catalyst is a 40% platinum carbon catalyst (40% is the mass ratio of heavy metal platinum to platinum carbon catalyst). The ink is liquid, the catalyst and Nafion ionomer are solid, and the ratio of solid to liquid is 10mg / ml. The ink is composed of isopropanol and water in a volume ratio of 3:1. The mass of Nafion ionomer accounts for 15% of the total solid mass. The adsorption amount of catalyst on the template is 0.5mg / cm 2 , dry and set aside.
[0074] The catalytic layer was transferred to the Nafion membrane by transfer method, with transfer pressure of 10t, transfer temperature of 135℃ and time of 3min. Then the membrane was soaked in 0.5M sulfuric acid for 10h and soaked in clean water for standby use. The sum of the channel thickness and the membrane electrode thickness was controlled to be 2mm. The straight channel part of the serpentine channel was controlled to be perpendicular to the water inlet and outlet directions, and the membrane electrode was assembled and tested.
[0075] The performance of the membrane electrode prepared in Example 3 was tested, and the results were similar to those in Example 1.
[0076] Embodiment 4:
[0077] Cut 10 aluminum plates of 10cm*1cm with a thickness of 0.3cm, polish and soak in 10% hydrogen peroxide solution for cleaning, then prepare 30mL 1M potassium hydroxide and equimolar urea, and hydrothermally react the ten aluminum plates therein respectively, the hydrothermal treatment temperature is 160°C, the hydrothermal treatment time is (10n+8) / 9 (n=1-10, t=2, T=12), specifically 2h, 28 / 9h, 38 / 9h, 16 / 3h, 58 / 9h, 68 / 9h, 26 / 3h, 88 / 9h, 98 / 9h and 12h. After rinsing and drying with ultrapure water, each template is equally impregnated with adsorbed anode slurry. The anode slurry includes ink, catalyst and Nafion ionomer. The catalyst is iridium oxide. The ink is liquid, the catalyst and Nafion ionomer are solid, and the ratio of solid to liquid is 10mg / ml. The ink is composed of isopropanol and water in a volume ratio of 3:1. The mass of Nafion ionomer accounts for 15% of the total solid mass. The mass of each template adsorption catalyst is (55*(5n+4) / Σ(5n+4))mg (n=1-10), specifically 11 / 7mg, 154 / 63mg, 209 / 63mg, 88 / 21mg, 319 / 63mg, 374 / 63mg, 143 / 21mg, 484 / 63mg, 539 / 63mg, 66 / 7mg. Dry and set aside.
[0078] Cut another 10cm*10cm aluminum plate with a thickness of 0.3cm. After polishing, soak it in a 10% hydrogen peroxide solution for cleaning. Then prepare 30mL of 1M potassium hydroxide and equimolar urea, and hydrothermally react the niobium plates in them. The hydrothermal treatment temperature is 160°C and the hydrothermal treatment time is 8 hours. After rinsing and drying with ultrapure water, the template is equally impregnated with adsorbed cathode slurry. The cathode slurry includes ink, catalyst and Nafion ionomer. The catalyst is a 40% platinum carbon catalyst (40% is the mass ratio of heavy metal platinum to platinum carbon catalyst). The ink is liquid, the catalyst and Nafion ionomer are solid, and the ratio of solid to liquid is 10mg / ml. The ink is composed of isopropanol and water in a volume ratio of 3:1. The mass of Nafion ionomer accounts for 15% of the total solid mass. The adsorption amount of catalyst on the template is 1mg / cm 2 , dry and set aside.
[0079] The catalytic layer was transferred to the Nafion membrane by transfer method, with transfer pressure of 10t, transfer temperature of 135℃ and time of 3min. Then the membrane was soaked in 0.5M sulfuric acid for 10h and soaked in clean water for standby use. The sum of the channel thickness and the membrane electrode thickness was controlled to be 1mm. The straight channel part of the serpentine channel was controlled to be perpendicular to the water inlet and outlet directions, and the membrane electrode was assembled and tested.
[0080] The performance of the membrane electrode prepared in Example 4 was tested, and the results were similar to those in Example 1.
[0081] Embodiment 5:
[0082] Cut 10 10cm*1cm niobium plates with a thickness of 0.5cm, polish them and soak them in 20% hydrogen peroxide solution for cleaning, then prepare 30mL 1M potassium fluorotantalate, add equimolar sodium oxalate to it, and hydrothermally react the ten niobium plates in it, the hydrothermal treatment temperature is 160℃, the hydrothermal treatment time is (10n+8) / 9 (n=1~10, t=2, T=12), specifically 2h, 28 / 9h, 38 / 9h, 16 / 3h, 58 / 9h, 68 / 9h, 26 / 3h, 88 / 9h, 98 / 9h and 12h respectively. After rinsing and drying with ultrapure water, spray the anode slurry on each template. The anode slurry includes ink, catalyst precursor and Nafion ionomer. The catalyst precursor is chloroiridic acid. The ink consists of isopropanol and water in a volume ratio of 3:1. In the anode slurry, the content of iridium is 8.5 mg / mL, and the content of Nafion ionomer is 1.8 mg / mL. The mass of each template adsorption catalyst is (55*(5n+4) / Σ(5n+4)) mg (n=1-10), specifically 11 / 7 mg, 154 / 63 mg, 209 / 63 mg, 88 / 21 mg, 319 / 63 mg, 374 / 63 mg, 143 / 21 mg, 484 / 63 mg, 539 / 63 mg, 66 / 7 mg. After drying, put it into a muffle furnace and calcine it at 450°C for 3 hours.
[0083] Cut another 10cm*10cm niobium plate with a thickness of 0.5cm, polish it and soak it in a 20% hydrogen peroxide solution for cleaning, then prepare 30mL1M potassium fluorotantalate, add an equal number of moles of urea to it, and hydrothermally react the niobium plates in it, the hydrothermal treatment temperature is 160℃, and the hydrothermal treatment time is 10 hours. After rinsing and drying with ultrapure water, the template is equally impregnated with adsorbed cathode slurry. The cathode slurry includes ink, catalyst and Nafion ionomer. The catalyst is a 40% platinum carbon catalyst (40% is the mass ratio of heavy metal platinum to platinum carbon catalyst). The ink is liquid, the catalyst and Nafion ionomer are solid, and the ratio of solid to liquid is 10mg / ml. The ink is composed of isopropanol and water in a volume ratio of 3:1. The mass of Nafion ionomer accounts for 15% of the total solid mass. The adsorption amount of catalyst on the template is 1mg / cm 2 , dry and set aside.
[0084] The catalytic layer was transferred to the Nafion membrane by transfer method, with transfer pressure of 10t, transfer temperature of 135℃ and time of 3min. Then the membrane was soaked in 0.5M sulfuric acid for 10h and soaked in clean water for standby use. The sum of the channel thickness and the membrane electrode thickness was controlled to be 1mm. The straight channel part of the serpentine channel was controlled to be perpendicular to the water inlet and outlet directions, and the membrane electrode was assembled and tested.
[0085] The performance of the membrane electrode prepared in Example 5 was tested, and the results were similar to those in Example 1.
[0086] Embodiment 6:
[0087] Cut 10 platinum plates of 10cm*1cm with a thickness of 0.4cm, polish them and soak them in 20% hydrogen peroxide solution for cleaning, then prepare 30mL 1M potassium fluorotantalate, add equimolar potassium oxalate to it, and hydrothermally react ten niobium plates in it, the hydrothermal treatment temperature is 160℃, the hydrothermal treatment time is (10n+8) / 9 (n=1~10, t=2, T=12), specifically 2h, 28 / 9h, 38 / 9h, 16 / 3h, 58 / 9h, 68 / 9h, 26 / 3h, 88 / 9h, 98 / 9h and 12h respectively. After rinsing and drying with ultrapure water, spray anode slurry on each template. The anode slurry includes ink, catalyst precursor and Nafion ionomer. The catalyst precursor is chloroiridic acid. The ink is composed of isopropanol and water in a volume ratio of 3:1. In the anode slurry, the iridium content is 8.5 mg / mL, and the Nafion ionomer content is 1.8 mg / mL. The mass of Ir in each template adsorption catalyst precursor is calculated as (85*(5n+4) / Σ(5n+4)) mg (n=1-10), which are 2.43 mg, 3.77 mg, 5.12 mg, 6.47 mg, 7.83 mg, 9.17 mg, 10.52 mg, 11.87 mg, 13.22 mg, and 14.57 mg, respectively. After drying, the mixture was placed in a muffle furnace and calcined at 450°C for 3 hours.
[0088] Cut another 10cm*10cm niobium plate with a thickness of 0.4cm, polish it and soak it in a 20% hydrogen peroxide solution for cleaning, then prepare 30mL of 1M potassium tantalate, add an equal number of moles of potassium oxalate to it, and hydrothermally react the niobium plates in it, the hydrothermal treatment temperature is 160℃, and the hydrothermal treatment time is 8 hours. After rinsing and drying with ultrapure water, the template is equally impregnated with adsorbed cathode slurry. The cathode slurry includes ink, catalyst and Nafion ionomer. The catalyst is a 40% platinum carbon catalyst (40% is the mass ratio of heavy metal platinum to platinum carbon catalyst). The ink is liquid, the catalyst and Nafion ionomer are solid, and the ratio of solid to liquid is 10mg / ml. The ink is composed of isopropanol and water in a volume ratio of 3:1. The mass of Nafion ionomer accounts for 15% of the total solid mass. The adsorption amount of catalyst on the template is 1mg / cm 2 , dry and set aside.
[0089] The catalytic layer was transferred to the Nafion membrane by transfer method, with transfer pressure of 10t, transfer temperature of 135℃ and time of 3min. Then the membrane was soaked in 0.5M sulfuric acid for 10h and soaked in clean water for standby use. The sum of the channel thickness and the membrane electrode thickness was controlled to be 1mm. The straight channel part of the serpentine channel was controlled to be perpendicular to the water inlet and outlet directions, and the membrane electrode was assembled and tested.
[0090] The performance of the membrane electrode prepared in Example 6 was tested, and the results were similar to those in Example 1.
[0091] Embodiment 7:
[0092] Cut 10 10cm*1cm niobium plates with a thickness of 0.5cm, polish them and soak them in 20% hydrogen peroxide solution for cleaning, then prepare 30mL 1M potassium fluorotantalate, add equimolar urea to it, and hydrothermally react the ten niobium plates in it, the hydrothermal treatment temperature is 160℃, and the hydrothermal treatment time is (10n+8) / 9 (n=1~10, t=2, T=12), specifically 2h, 28 / 9h, 38 / 9h, 16 / 3h, 58 / 9h, 68 / 9h, 26 / 3h, 88 / 9h, 98 / 9h and 12h respectively. After rinsing and drying with ultrapure water, each template is equally impregnated with adsorbed anode slurry. The anode slurry includes ink, catalyst precursor and Nafion ionomer. The catalyst precursor is chloroiridic acid. The ink is composed of isopropanol and water in a volume ratio of 3:1. In the anode slurry, the content of iridium is 8.5 mg / mL, and the content of Nafion ionomer is 1.8 mg / mL. The mass of Ir in each template adsorption catalyst precursor is calculated as (85*(5n+4) / Σ(5n+4)) mg (n=1-10), which are 2.43 mg, 3.77 mg, 5.12 mg, 6.47 mg, 7.83 mg, 9.17 mg, 10.52 mg, 11.87 mg, 13.22 mg, and 14.57 mg, respectively. After drying, it is placed in a muffle furnace and calcined at 550°C for 3 hours.
[0093] Cut another 10cm*10cm niobium plate with a thickness of 0.5cm. After polishing, soak it in a 20% hydrogen peroxide solution for cleaning. Then prepare 30mL of 1M potassium tantalate, add an equal number of moles of urea to it, and hydrothermally react the niobium plates in it. The hydrothermal treatment temperature is 160°C and the hydrothermal treatment time is 10 hours. After rinsing and drying with ultrapure water, the template is equally impregnated with adsorbed cathode slurry. The cathode slurry includes ink, catalyst precursor and Nafion ionomer. The catalyst precursor is chloroplatinic acid. The ink consists of isopropanol and water in a volume ratio of 3:1, in which the platinum content is 8.5mg / mL and the Nafion ionomer content is 1.8mg / mL. The adsorption amount of the catalyst on the template is 1mg / cm 2, dry and set aside.
[0094] The catalytic layer was transferred to the Nafion membrane by transfer method with transfer pressure of 20t, transfer temperature of 135℃ and time of 3min. Then the membrane was soaked in 0.5M sulfuric acid for 10h and soaked in clean water for standby use. The sum of the channel thickness and membrane electrode thickness was controlled to be 2mm. The straight channel part of the serpentine channel was controlled to be perpendicular to the water inlet and outlet directions for membrane electrode assembly and testing.
[0095] The performance of the membrane electrode prepared in Example 7 was tested, and the results were similar to those in Example 1.
[0096] The following examples are provided only to illustrate the present invention and are not intended to limit the scope of protection defined by the appended claims.
Claims
1. A gradient ordered membrane electrode for PEM water electrolysis, characterized in that: The invention comprises a gradient ordered anode catalyst layer, wherein the anode catalyst layer is composed of a plurality of ordered regions, the catalyst layer of each ordered region is composed of a uniformly distributed nanoarray, the height of the nanoarray in each ordered region is the same, and the thickness gradient of the catalyst layer in the ordered region increases from the liquid inlet to the liquid outlet.
2. A method for constructing and integrating a gradient ordered membrane electrode for PEM water electrolysis, characterized in that: The steps include: Step S1, preparing anode template S1.1 According to the actual load size D×L, select N suitable substrates, each of which has a width of D / N and a length of L; where D is the width of the electrode, L is the length of the electrode, and N is a positive integer greater than 2; S1.2 Prepare an ordered nanoarray growth solution or a substrate ordered etching solution, construct array channels by hydrothermal method or ordered etching method, and adjust the size of the nanoarray by controlling the processing time to obtain an ordered template sequence; the processing time is the hydrothermal processing time or the etching processing time, and the processing time of the nth substrate is Wherein, n is any positive integer from 1 to N, t is the processing time of the first substrate, and T is the processing time of the Nth substrate; S1.3 The anode slurry is impregnated or sprayed on the template, and the anode catalyst is loaded on N ordered template sequences, and the loading amount increases with the extension of the template treatment time. The ordered template sequences are arranged in the order of treatment time to assemble into an anode template with an actual loading size of D×L; Step S2, preparing cathode template Step S3, preparing membrane electrode Step S4, integration S4.1 Calibrate the membrane electrode thickness in each gradient range, and customize the corresponding flow field after clarifying the thickness gradient, so that the sum of the flow field thickness and the membrane electrode thickness is the same in each area; S4.2 Place the assembled membrane electrode / stack in the order of increasing anode loading from the liquid inlet to the liquid outlet.
3. A gradient ordered membrane electrode construction and integration method for PEM water electrolysis according to claim 2, characterized in that: The substrate in step S1 and / or step S2 is selected from niobium plate, aluminum plate, tungsten plate, titanium plate, tantalum plate, platinum plate, and iridium plate.
4. A gradient ordered membrane electrode construction and integration method for PEM water electrolysis according to claim 2, characterized in that: In the step S1.2, the ordered nanoarray growth solution is chloride, sulfate, phosphate, acetate, tungstate, fluorotantalate, or chloroplatinate of niobium, tungsten, titanium, tantalum, platinum, zirconium, chromium, or manganese.
5. A gradient ordered membrane electrode construction and integration method for PEM water electrolysis according to claim 2, characterized in that: The hydrothermal treatment time t of the first substrate is 1-8 hours, and the hydrothermal treatment time T of the Nth substrate is 12-36 hours.
6. A gradient ordered membrane electrode construction and integration method for PEM water electrolysis according to claim 2, characterized in that: In step S1.3, the noble metal loading in the nth ordered template sequence is mST n / ΣT n , m is the average load per unit area, S is the actual load area D×L, T n is the hydrothermal treatment time of the nth substrate, m is 0.1 mg / cm 2 ~4mg / cm 2 .
7. A gradient ordered membrane electrode construction and integration method for PEM water electrolysis according to claim 2, characterized in that: In step S4.1, the sum of the thickness of the flow channel and the membrane electrode is 0.1 mm to 5 mm.
8. A gradient ordered membrane electrode construction and integration method for PEM water electrolysis according to claim 2, characterized in that: In step S4.1, a serpentine flow field is used, and the width of the serpentine flow field is D / (N×X), where X is the number of times the flow field passes through the surface of each gradient catalyst.
9. A gradient ordered membrane electrode construction and integration method for PEM water electrolysis according to claim 8, characterized in that: X is an integer of 2-10.
10. A gradient ordered membrane electrode construction and integration method for PEM water electrolysis according to claim 2, characterized in that: In step S4.2, the straight flow channel portion of the serpentine flow field is perpendicular to the water inlet and outlet directions.
Citation Information
Patent Citations
Ordered anode catalyst layer of PEM water electrolysis membrane electrode and preparation method and application thereof
CN112981449A
Preparation method of PEM water electrolysis hydrogen production low-iridium membrane electrode
CN115125549A